Hubungan Ekspansi Jaringan Kantor dan Kinerja Keuangan Terhadap Pertumbuhan Aset Bank Syariah - Dwi Nuraini Ihsan (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
This study tests Islamic banks in Indonesia for the period 2015 – May 2019 which aims to prove the influence of bank office network expansion and bank financial performance which is proxied by the ratio of CAR, BOPO, NOM and ROA to the growth of Islamic bank assets. The strategy of expanding the bank office network and achieving the performance of Islamic banks will have an impact on the growth of assets owned by the bank. This relationship analysis is basically to examine the extent of the relationship between bank expansion and bank ratios to the growth rate of assets. With a 5% significance level, it is obtained that NOM and ROA do not have a significant effect on asset growth.